2017
DOI: 10.15406/jsrt.2017.02.00081
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calcium Bio-Minerals in Regenerative Medicine and Tissue Engineering

Abstract: Present review article emphasize role of biominerals in regenerative medicine and tissue engineering. Among all biominerals calcium is essential for body growth and development. It also performs many fundamental functions in cellular metabolism. Inside cell organic matrix is calcified by calcium phosphate minerals. It also embeds bone cells which participate in the maintenance and organization of bone. This article also emphasizes use of hydroxyapatite a natural mineral used as a bone-building supplement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…The characterization (XRD, FTIR, SEM and EDS) confirms that HApC and HApS are hydroxyapatite (HAp) and carbonated hydroxyapatite (CHAp) plus ( +) calcite respectively. The lattice constants for HApC and HApS correspond to a unit cell volume of 527.6838Å 3 and 521.3976Å 3 2− could substitute at B-site and or OH-site (A-site) in HAp depending on the thermodynamic conditions and how charges are compensated. For HApS, Ca 2+ was given out for charge compensation, and because CO 3 2− has a smaller ionic size, it is oriented at B-site parallel to the c-axis of the hexagonal unit cell for stability and that results in a reduced unit cell volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization (XRD, FTIR, SEM and EDS) confirms that HApC and HApS are hydroxyapatite (HAp) and carbonated hydroxyapatite (CHAp) plus ( +) calcite respectively. The lattice constants for HApC and HApS correspond to a unit cell volume of 527.6838Å 3 and 521.3976Å 3 2− could substitute at B-site and or OH-site (A-site) in HAp depending on the thermodynamic conditions and how charges are compensated. For HApS, Ca 2+ was given out for charge compensation, and because CO 3 2− has a smaller ionic size, it is oriented at B-site parallel to the c-axis of the hexagonal unit cell for stability and that results in a reduced unit cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…Bone tissue engineering is the field of regenerative medicine where damaged or a diseased bone is repaired by restoring new tissue using engineered scaffolds, stem cells and biomolecules [1][2][3]. The most successful scaffolds are fabricated from biomaterials that imitate the human extracellular matrix (ECM) more successfully [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…15 In most human tissues the volume occupied by cells is substantially smaller compared to the volume of the surrounding extracellular matrix (ECM), like in cartilage which contains about 1–2% of cells 16 or calcified bone which comprises about 25% organic matrix (of which 2–5% contributes to cells), 5% water and 70% inorganic mineral. 17 Now, the pressing question emerges, which addresses the fueling of the dynamic and complex ECM with metabolic energy, a space which does not contain ATP-generating mitochondria. Even more, the ECM is, as outlined above, poor in ATP, and if present in this compartment, this nucleotide is exposed to the extracellular or cell membrane-bound alkaline phosphatase (ALP [EC 3.1.3.1]) and the cell membrane glycoprotein-1 phosphodiesterase [EC 3.1.4.1]/nucleotide pyrophosphatase [EC 3.6.1.9].…”
Section: Introductionmentioning
confidence: 99%
“…2, Additional le 3). It was obvious that minerals played an important role in biomineral tissue development and skeletal system development [20,21]. We found that other GO functions may also be indirectly related to transcellular transport of ion and minerals (or metals).…”
Section: Kegg Pathway and Go Analysis Of Pm25 Resistance Genesmentioning
confidence: 87%